PENGEMBANGAN STARTUPPRENEURSHIP MAHASISWA MELALUI PROGRAM WIRAUSAHA MERDEKA (WMK) BERBASIS GROWTH ENTERPRENEURIAL EDUCATION - Fatmawati, Siti Ifa; Fatimah, Nurul (Jurnal Ekonomi dan Pendidikan, 2025)
Wirausaha Merdeka is a program from the Ministry of Education and Culture of the Republic of Indonesia that aims to foster interest, build, and develop students' entrepreneurial spirit. One of the universities that implements the wirausaha merdeka program is the Semarang State Polytechnic (Polines) with the theme of character-based entrepreneurship, accelerating with technology, and business ecosystems using a systematic entrepreneurship education growth strategy. The purpose of this study was to determine the implementation of the theme raised and the growth strategy of the entrepreneurship education network developed in the Independent Entrepreneurship program at the Semarang State Polytechnic. This research was conducted while the researcher was participating in the wirausaha merdeka program batch 2 program at Polines using a qualitative mix method approach with participant observation, interview, documentation, and survey methods. Through this program, Polines succeeded in making the program a success and providing benefits to the participants, especially skills in the field of entrepreneurship.